Percutaneous Urine Sampling from Renal Pelvis: A Minimally-Invasive Method to Determine the Origin of Post-Transplant Proteinuria - Babaei Jandaghi, Ali; Badeli, Hamidreza; Hassanzadeh Rad, Afagh; Pourghorban, Ramin (Journal of Pediatric Nephrology, 2019)
A 14-year-old boy with end-stage renal disease secondary to focal segmental glomerulosclerosis complicated with heavy proteinuria received a non- related living kidney transplantation. Postoperatively he continued to excrete higher level of proteinuria. Allograft biopsy showed mild mesangial expansion and hypercellularity. Urine sample was collected from allograft renal pelvis under local anesthesia and ultrasound guidance. Based on the importance of heavy proteinuria and lack of definite method of differentiating its source during the early weeks after kidney transplantation, it seems that percutaneous renal pelvis urine sampling may be noted as a preferred method of detecting the source of proteinuria. Keywords: Focal Segmental Glomerulosclerosis; Kidney Transplantation; Ultrasonography; Proteinuria; Allografts.